PENGARUH LATIHAN JUGGLING TERHADAP KETERAMPILAN DRIBBLING FUTSAL STUDI EKSPERIMEN PADA PESERTA EKSTRAKURIKULER FUTSAL SMA KEMALA BHAYANGKARI - Epan, Epan; Triansyah, Andika; Puspa H, Fitriana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe problem discussed in this study is not yet know whether there is an influence of juggling exercises on dribbling skills at kemala bhayangkari high school? The purpose of this research is to find out whether there is an effect of juggling exericises on the futsal dribbling skill of experimental studies of futsal extracuricular participants in bhayangkari. This used an experimental method with the one grup pretest and postest design. The population in this study were futsal extracuricular students of kemala bhayangkari high school, totaling 30 students, with a sample of 15 students. Analysis of the data used in this research is t-test. The results of this study are the influence of juggling exercises on dribbling skils based on tcount>ttable is 8.61.> 1.7613 with an average pretest score of 19.4 and an average postest value of 17.5. it can be concluded that Ha = accepted an Ho = rejected. Means there is an influence of juggling exercises on futsal dribbling skills.Keywords: Dribbbling, Futsal, Juggling